Resilience Of Working Mothers with Autistic Spectrum Disorder: Resiliensi Ibu Bekerja yang Memiliki Anak Autistic Spectrum Disorder - Siska Dwi Wahyuni Sugianto; Eko Hardi Ansyah (Academia Open, 2022)
A mother who has a child with ASD (Autistic Spectrum Disorder) has a heavier responsibility in terms of parenting and will go through a certain process. Handle these conditions, conditions are needed to be able to accept the conditions is resilience. This study aims to determine the description of resilience and the factors that influence resilience in working mothers who have children with ASD. Using qualitative method with a phenomenological type, determining the subject using a purposive sampling technique using 3 subjects working mothers who have children with ASD. Data collection methods in the form of interviews and observations. The results of the third study show that there is a picture of resilience in the three subjects who are able to accept their child's condition and rise from their previous condition to be better. That not all subjects have the seven aspects of resilience, each subject has a different dominance. Highlights: Resilience in parenting: The study explores the resilience of working mothers raising children with ASD, emphasizing their ability to accept their child's condition and adapt to the challenges they face. Influential factors: The research aims to identify the factors that influence the resilience of these mothers, considering individual differences and unique experiences that shape their responses to the situation. Diverse resilience aspects: The findings reveal that while all subjects displayed resilience, the aspects of resilience varied among them, highlighting that resilience is a multidimensional construct with different dominant factors for each individual. Keywords: Resilience, Working mothers, Autism Spectrum Disorder (ASD), Qualitative method, Phenomenological approach.